Contextualising the Decisions of the Native Land Court: The Chatham Islands Investigations of 1870 - Boast, Richard P (Victoria University of Wellington Law Review, 2010)
One of the outcomes of the Lost Cases project at the Faculty of Law at Victoria University will be an edition of nineteenth century judgments of the Native Land Court. These decisions have never been reported before. The anticipated date of publication is mid- to late- 2011, and the volume will report leading decisions of the Native Land Court, Compensation Court, and associated bodies from 1865 to 1894. The date of 1894 has been selected as a cut-off for the reason that the Native Land Court Act 1894 established a new appellate body, the Native Appellate Court – today the Maori Appellate Court – which began issuing appellate judgments immediately. Until this point all appeals had been by means of rehearings and no formal appellate structure existed. Future volumes will report decisions of the Native Land Court and Native Appellate Court down to the present day. This article explores the current state of the historiography relating to the Native Land Court, and by reference to the Chatham Islands Investigation of 1870, suggests that a more complex and nuanced approach to the work of the Court is needed. The full texts of the Chatham Islands judgments of 1870 are printed as an Appendix.